2017
DOI: 10.1177/1758573217701107
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, management and complications of distal humerus lateral condyle fractures in children

Abstract: We review the diagnosis, evaluation and management of paediatric lateral condylar fractures. The complications of these fractures are also discussed, including the management of fracture non-union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
0
32
1
Order By: Relevance
“…CRPP has shown several advantages over ORIF, including less dissection of soft tissue around the fragment, low risk of vessel damage, low risk of non-union and AVN of distal humerus physes, shorter operating room times, and avoidance of an open incision with unaesthetic scar [ 15 , 19 ], avoidance of another operation or anesthesia because of hardware removal. The present study demonstrated that closed reduction and percutaneous pinning is a safe and efficient technique for treating LCHFs with displacement more than 4 mm, and more than 3/4 of Song stage V or Jakob type III patients can avoid an incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRPP has shown several advantages over ORIF, including less dissection of soft tissue around the fragment, low risk of vessel damage, low risk of non-union and AVN of distal humerus physes, shorter operating room times, and avoidance of an open incision with unaesthetic scar [ 15 , 19 ], avoidance of another operation or anesthesia because of hardware removal. The present study demonstrated that closed reduction and percutaneous pinning is a safe and efficient technique for treating LCHFs with displacement more than 4 mm, and more than 3/4 of Song stage V or Jakob type III patients can avoid an incision.…”
Section: Discussionmentioning
confidence: 99%
“…However, closed reduction and percutaneous pinning (CRPP) for treating pediatric lateral condylar humerus has been reported only in a few studies [ 9 18 ]. CRPP has shown several advantages over ORIF, including less dissection of soft tissue around the fragment, low risk of vessel damage, low risk of non-union and avascular necrosis (AVN) of distal humerus physeal, shorter operating room times, and avoidance of an open incision with an unaesthetic scar [ 15 19 ]. In most studies, this technique was used only in cases with displacement between 2 and 4 mm [ 9 , 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRPP has shown several advantages over ORIF, including less dissection of soft tissue around the fragment, low risk of vessel damage, low risk of non-union and AVN of distal humerus physes, shorter operating room times, and avoidance of an open incision with unaesthetic scar [15,19], avoidance of another operation or anesthesia because of hardware removal. The present study demonstrated that closed reduction and percutaneous pinning is a novel and feasible technique for treating LCHFs with displacement more than 4 mm, and more than 3/4 of Song stage V or Jakob type III patients can avoid an incision.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRPP for treating pediatric lateral condylar humerus has been reported only in a few studies [9][10][11][12][13][14][15][16][17][18]. CRPP has shown several advantages over ORIF, including less dissection of soft tissue around the fragment, low risk of vessel damage, low risk of non-union and avascular necrosis (AVN) of distal humerus physeal, shorter operating room times, and avoidance of an open incision with an unaesthetic scar [15][16][17][18][19]. In most studies, this technique was used only in cases with displacement between 2-4 mm [9,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…17 In the past, the main treatment for lateral condylar fractures with non-union was osteotomy surgery to correct elbow valgus deformity. 18 However, osteotomy surgery alone does not address instability of the elbow, and may result in detrimental impact on the patient quality of life. Conversely, the two staged surgery initially manages the stability of the elbow and then focuses on the deformity correction.…”
Section: Discussionmentioning
confidence: 99%